New Weighted Total Acceleration on Momentum Euler Equation for Formulating Water Wave Dispersion Equation - Hutahaean, Syawaluddin (International Journal of Advanced Engineering Research and Science, 2021)
In this present study, weighted total acceleration for Kinematic Free Surface Boundary Condition (KFSBC) and in momentum Euler equation was formulated. Furthermore, by using both aforementioned equations, the nonlinear water wave dispersion equation was then formulated. The wavelength obtained from dispersion equation is determined by weighting coefficient. The weighting coefficient value was determined by using the maximum wave height and critical wave steepness criteria which have been obtained from the previous studies.